Operative Versus Nonoperative Treatment of Displaced Intra-Articular Calcaneal Fractures: A Meta-Analysis of Randomized Controlled Trials. Issue 3 (March 2016) - Zhang, Wei; Lin, Feng; Chen, Erman; Xue, Deting; Pan, Zhijun
Abstract : Objectives: To compare the clinical outcomes of operative and nonoperative treatment for displaced intra-articular calcaneal fractures (DIACFs). Data Sources: PubMed, Embase, Cochrane library, and ClinicalTrial.gov. Study Selection: Randomized controlled trials comparing operative and nonoperative treatment for DIACFs. Data Extraction: Information on study methods and clinical outcomes. Data Synthesis: We performed data synthesis on relevant clinical outcomes. Weighted mean differences with 95% confidence intervals were calculated for continuous data and relative risks with 95% confidence intervals were calculated for dichotomous data. A fixed-effect model or a random-effect model was used. Results: Seven randomized controlled trials involving 908 patients were included. Operative treatment for DIACFs reduced problems associated with shoe wear and increased walking ability but increased the risks of overall complications and infection. There were no significant differences between the groups in American Orthopaedic Foot and Ankle Society scores, The Short Form (36) Health Survey, return to work, rate of subsequent subtalar fusion, or the rate of reflex sympathetic dystrophy. Conclusions: This meta-analysis documented that when surgery was performed correctly, better shoe wear and improved walking ability could be expected. These outcomes seemed to be based on the surgeon's ability to obtain an acceptable reduction. Benefits were tempered by the increase in wound complications associated with this intervention. Level of Evidence: Therapeutic Level II. See Instructions for Authors for a complete description of levels of evidence. Abstract : Supplemental Digital Content is Available in the Text.